2022
DOI: 10.1057/s41287-022-00532-2
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relationship Between Social Protection and Social Cohesion: Introduction to the Special Issue

Abstract: While there is substantial evidence of the effect of social protection on poverty and vulnerability, limited research has focused on societal outcomes. This paper serves as introduction to a special issue (SI) examining the relationship between social protection and social cohesion in low- and middle-income countries. Over the last years, social cohesion has emerged as a central goal of development policy. The introduction and the papers in the SI use a common definition of social cohesion as a multi-faceted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…: 12-13). As Burchi et al (2022) note, peace is also an outcome of social cohesion: 'a socially cohesive society is one in which individuals can have different identities and yet live together in a peaceful way' (ibid. : 1200).…”
Section: Conflict-transformative Social Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…: 12-13). As Burchi et al (2022) note, peace is also an outcome of social cohesion: 'a socially cohesive society is one in which individuals can have different identities and yet live together in a peaceful way' (ibid. : 1200).…”
Section: Conflict-transformative Social Protectionmentioning
confidence: 99%
“…(2) targeting processes that involve consultation and include trusted local public authorities; and (3) appeals and grievance mechanisms that are rule-bound and accessible to local actors, including both those who are targeted and those who are not. (Burchi et al 2022). In Kenya, the HSNP's theory of change makes no reference to social cohesion.…”
Section: Conflict-transformative Social Protectionmentioning
confidence: 99%
“…On the whole, reviews and evaluations of the NSNP cash transfer programmes have found that, while community-level tensions can arise (usually linked to targeting, and in particular when the support does not cover broad-based need in communities), there have been broadly positive impacts on social capital, inclusion and cohesion (Pavanello et al 2016;Strupat 2021;UNHCR 2019;Merttens et al 2018: 53-55). However, as with other countries, work is still needed to build the evidence base on how and under what conditions cash transfers can strengthen social capital, inclusion and the state-citizen contract (Pavanello et al 2016(Pavanello et al : 1158Burchi et al 2022).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Environmental social cohesion operates at the neighborhood or community level. The environment can be interpreted as a geographical place with a social and cultural meaning for residents and non-residents alike and is a subsection of a larger place [60]. Social cohesion is important.…”
Section: Communal Space As An Environmental and Family Control Spacementioning
confidence: 99%